Making Worlds : Global Invention in the Early Modern Period - Wilson, Bronwen; Vanhaelen, Angela (Book collections on Project MUSE., 2022)
"Taking into account the destructive powers of globalization, Making Worlds considers the interconnectedness of the world in the early modern period. This collection examines the interdisciplinary phenomenon of making worlds, with essays from scholars of history, literary studies, theatre and performance, art history, and anthropology. The volume advances questions about the history of globalization by focusing on how the expansion of global transit offered possibilities for interactions that included the testing of local identities through inventive experimentation with new and various forms of culture. Case studies show how the imposition of European economic, religious, political, and military models on other parts of the world unleashed unprecedented forces of invention as institutionalized powers came up against the creativity of peoples, cultural practices, materials, and techniques of making. In doing so, Making Worlds offers an important rethinking of how early globalization inconsistently generated ongoing dynamics of making, unmaking, and remaking worlds."--